DAMPAK KEBIJAKAN OJK NOMOR 4 TAHUN 2023 TERHADAP PENGUATAN KEUANGAN SYARIAH NASIONAL - Vika Miftahul Jannah; Stevanus Antoni.R; Anne Monika Fristy; Henry Martin Adriansyah (Jurnal Akuntansi Kompetif, 2026)
This study aims to examine the impact of the implementation of Financial Services Authority Regulation (POJK) No. 4 of 2023, which amends the provisions on Collective Investment Contracts (CIC), on strengthening the national Islamic finance industry. This research employs a descriptive qualitative approach based on literature review and documentary analysis of regulatory texts and official reports issued by the Financial Services Authority (OJK). The findings indicate that POJK No. 4 of 2023 positively contributes to improving the governance framework of CIC-based investment products through the enhancement of registration procedures, reporting mechanisms, and disclosure requirements. This regulatory strengthening increases the effectiveness of Sharia compliance supervision, promotes transparency in the Islamic capital market, and enhances investor protection. Indirectly, the policy fosters greater confidence among market participants and investors in Islamic financial products, thereby reinforcing the role of the Islamic capital market within the national financial ecosystem. However, the full potential of the regulation remains constrained by challenges such as limited public literacy on Islamic finance, relatively high compliance costs for industry players, and the need for stronger inter-institutional coordination. Therefore, comprehensive supporting policies are essential to sustain the long-term development of the Islamic finance sector